The basis for a constructive relationship between management consultants and clients (SMEs) - Renato J. Lopes da Costa; Álvaro Lopes Dias; Leandro Pereira; José Santos; Isabel Miguel (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
In a historical retrospective, although the existing literature calls the management consulting industry an extraordinary sector and a unique phenomenon in the business context, in fact these statements are not accompanied by a number of academic studies that emphasize the importance of the effective management consultant's work. To battle the lack of studies in this emerging area, this article aims to understand the most important factors from the perspective of consultants and managers to build successful relationships in management consulting projects. Semi-structured interviews and questionnaires were conducted to management consultants and SME managers. Our findings suggests competence and experience of consultants, their ability to understand clients, their professionalism and credibility, the transparency of the processes, values and goals they can put in the performance of their work are the five key factors for building successful relationships.
Keywords: L22; L25; 650; management consulting; relationships; strategy-as-practice